Manager-subordinate trust : a global perspective - Cardona, Pablo, 1964-; Morley, Michael. (Routledge global human resource management series, 2013)
"This volume in the Routledge Global Human Resource Management Series is dedicated to analyzing the process of trust development between managers and subordinates in different countries of the main cultures of the world. Behaviors and trust are linked in a process that can reinforce or diminish the trust between the two parties. This book examines that process in an array of countries, contextualizing each setting through a brief historical, institutional, and cultural overview and analyzing the universal and culturally-specific elements of the manager-subordinate relationship"--